Dental plaque score index differences in children with mental retardation using two types toothbrush - Permata, Ardita Dyna; Sukmasari, Susi; Suwargiani, Anne Agustina; Setiawan, Arlette Suzy Puspa Pertiwi (Padjadjaran Journal of Dentistry, 2020)
Introduction: Most of the mentally retarded children may not brush their tooth correctly. They need parents or caregivers to help and supervise the tooth brushing process to reduce the accumulation of dental plaque which may lead to oral diseases. This research was aimed to analyse the most effective toothbrush between parents’ toothbrush and regular toothbrush on children with mental retardation. Methods: This research was quasi-experimental with the blind method. Twenty-nine students with mental retardation consisted of boys and girls of YPLB Cipaganti Special Needs School-C (SLB-C) were selected with total sampling. Each individual was divided randomly and being given the parents’ toothbrush and regular toothbrush. Parents were responsible for brushing their children’s teeth during the period of the study. Plaque scoring was performed on the seventh day. The wash-out period was initiated after the seventh day for one week. Each group was given a different toothbrush from their first toothbrush, and the plaque scoring was performed on the first and seventh day. Plaque scoring was assessed using the Greene Vermillion Index. The data obtained were tested with the Wilcoxon and Mann-Whitney tests. Results: An average difference of plaque index before and after using parents’ toothbrush was 0.3, and the average difference of plaque index before and after using a regular toothbrush was 0.4. There was no significant difference in plaque index changes between these two toothbrushes (p-value > 0.05). Conclusion: Two types of toothbrushes, which are parents’ toothbrush and regular toothbrush are able to reduce plaque.